CdSe / CdxZn1-xS quantum rod with high polarization degree and high luminous efficiency and preparation method of CdSe / CdxZn1-xS quantum rod
By coating the CdSe core with a CdxZn1-xS alloy shell layer and controlling the growth process, the problems of low luminescence efficiency and polarization degree of quantum rods were solved, and the preparation of CdSe/CdxZn1-xS quantum rods with high polarization degree and high luminescence efficiency was achieved.
Patent Information
- Application Number
- CN202510766511.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-10
- Publication Date
- 2025-09-12
AI Technical Summary
The luminous efficiency and polarization degree of existing quantum rods are low, especially CdSe/CdS/ZnS quantum rods, which are affected by defects caused by shell separation and are difficult to reach the level of traditional quantum dots.
A CdxZn1-xS alloy shell is coated on the outside of the CdSe core. By controlling the order of adding different precursors, uninterrupted growth is achieved, reducing surface defects caused by shell lattice mutations and improving luminous efficiency and polarization.
The prepared CdSe/CdxZn1-xS quantum rods have a photoluminescence quantum yield of over 90% and a polarization degree of over 0.75, significantly improving the luminescence efficiency and polarization degree.
Smart Images

Figure CN120624020A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of quantum rod preparation, and in particular to a CdSe / Cd x Zn 1-x S quantum rod and preparation method thereof. Background Art
[0002] Quantum rods are rod-shaped quantum dot materials, whose sizes are usually on the nanometer scale. The quantum confinement effect makes quantum rods have excellent luminescence properties similar to traditional quantum dots, such as high brightness and narrow linewidth. At the same time, compared with traditional quantum dots, quantum rods have anisotropic shapes, which makes quantum rods exhibit polarized emission characteristics and are expected to be used in the production of polarized light-emitting devices. However, due to the larger specific surface area, quantum rods are more affected by surface defects, so their luminescence efficiency is usually lower than that of traditional quantum dots. To address this problem, the current solution is usually to coat the outer layer of the quantum rod with a semiconductor shell with a wider bandgap, such as coating a CdS shell and / or ZnS shell on the outside of a CdSe quantum rod, so as to confine the excitons in the quantum rod to the central region to prevent them from being affected by surface states. Compared with CdSe / CdS quantum rods and CdSe / ZnS quantum rods, the luminous efficiency of CdSe / CdS / ZnS quantum rods is relatively higher, but still lower than that of quantum dots themselves. This is because the shells of CdS and ZnS in CdSe / CdS / ZnS quantum rods are relatively separated, which makes the quantum rods have certain defects and has a certain impact on their luminous efficiency. Based on this, a high polarization degree and high luminous efficiency CdSe / CdS / ZnS quantum rod with high luminous efficiency is proposed. x Zn 1-x S quantum rod and preparation method thereof. Summary of the Invention
[0003] In order to solve the above technical problems, the present invention proposes a CdSe / Cd x Zn 1-x S quantum rod and its preparation method, by coating CdSe core with Cd x Zn 1-x The S alloy shell structure improves the polarization degree and luminous efficiency of the quantum rod.
[0004] The present invention specifically adopts the following technical solutions:
[0005] A high polarization degree and high luminous efficiency CdSe / Cd x Zn 1-x The preparation method of S quantum rods comprises the following steps:
[0006] (1) preparing a CdO precursor solution under an inert gas environment and heating it to a reaction temperature of 350±20° C., then sequentially injecting tri-n-octylphosphine and a CdSe precursor solution to obtain a first mixed solution;
[0007] (2) slowly adding a Zn precursor solution to the first mixed solution of step (1) to obtain a second mixed solution;
[0008] (3) Octadecene was first injected into the second mixed solution of step (2) to dilute it, and the reaction temperature was cooled to 300±20°C, and then the mixed solution of octadecene and S precursor solution was slowly added dropwise. After the addition was completed, the reaction was stopped to obtain CdSe / Cd x Zn 1-x S quantum rod, where 0<x<1;
[0009] (4) After the reaction is completed, cool to room temperature and purify the obtained CdSe / Cd x Zn 1-x S quantum rod.
[0010] Furthermore, the CdO precursor solution in step (1) is a mixed solution formed by heating and dissolving CdO, octadecylphosphonic acid, hexylphosphonic acid, and tri-n-octylphosphine oxide, and the mass ratio of CdO, octadecylphosphonic acid, hexylphosphonic acid, and tri-n-octylphosphine oxide is 1:10-18:3-5:130-190.
[0011] Furthermore, the mass of tri-n-octylphosphine injected alone in step (1) is 0.3 to 0.5 times the mass of the CdO precursor solution.
[0012] Furthermore, in step (1), the CdSe precursor solution is a mixed solution formed by heating and dissolving CdSe seeds, sulfur powder, and tri-n-octylphosphine, the mass ratio of CdSe seeds, sulfur powder, and tri-n-octylphosphine is 1:2-3.5:100-160, and the amount of CdSe precursor solution added is 0.3-0.5 times the mass of the CdO precursor solution.
[0013] Furthermore, in step (2), the Zn precursor solution is a mixed solution formed by heating and dissolving zinc acetate, octadecene, and oleic acid, the mass ratio of zinc acetate, octadecene, and oleic acid is 1:3-5:3.5-6, and the amount of the Zn precursor solution added is 0.9-1.3 times the mass of the CdO precursor solution.
[0014] Furthermore, the total amount of octadecene in step (3) is 0.5 to 0.8 times the mass of the Zn precursor solution added in step (2), and 2 / 3 of the octadecene is added for the first time for dilution, and the remaining 1 / 3 of the octadecene is mixed with the S precursor solution.
[0015] Furthermore, the S precursor solution in step (3) is a mixed solution formed by heating and dissolving sulfur powder and tri-n-octylphosphine, the mass ratio of sulfur powder to tri-n-octylphosphine is 1:10-15, and the amount of S precursor solution added is 0.1-0.15 times the mass of the Zn precursor solution added in step (2).
[0016] Furthermore, in step (2), the dropping speed of the Zn precursor solution is 6-12 mL / h, and the dropping speed of the mixed solution of octadecene and S precursor solution is 4-8 mL / h.
[0017] The present invention also provides a CdSe / Cd with high polarization degree and high luminous efficiency. x Zn 1-x S quantum rod, including CdSe core and Cd coated outside the CdSe core x Zn 1-x S shell.
[0018] Furthermore, the CdSe / Cd x Zn 1-x The photoluminescence quantum yield of the S quantum rod reaches more than 90%, and the polarization degree reaches more than 0.75.
[0019] The present invention has the following beneficial effects:
[0020] The present invention proposes a CdSe / Cd x Zn 1-x The preparation method of S quantum rods is to continuously grow CdS outside the CdSe core by controlling the addition order of different precursors. x Zn 1-x S alloy shell structure, which can effectively passivate the core surface while reducing the surface defects caused by shell lattice mutation, thereby improving its luminous efficiency and having a higher polarization degree; the CdSe / Cd prepared by the present invention x Zn 1-x The photoluminescence quantum yield of the S quantum rod reaches more than 90%, and the polarization degree reaches more than 0.75. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0022] Figure 1 The CdSe / Cd prepared in Example 1 x Zn1-x Schematic diagram of the structure of the S quantum rod;
[0023] Figure 2 The CdSe / Cd prepared in Example 1 x Zn 1-x HAADF-STEM micrographs of S quantum rods, where (a) is a dark-field TEM image, (b) is a distribution diagram of S and Se elements in the quantum rods, and (c) is a distribution diagram of Zn and Cd elements in the quantum rods.
[0024] Figure 3 The CdSe / Cd prepared in Example 1 x Zn 1-x Atomic-resolution TEM images of S quantum rods, where (a) and (b) are the lattice structures taken along different crystal directions, respectively;
[0025] Figure 4 The CdSe / Cd prepared in Example 1 x Zn 1-x Absorption and emission spectra of S quantum rods. DETAILED DESCRIPTION
[0026] The present invention provides a CdSe / Cd x Zn 1-x S quantum rod and its preparation method, in order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0027] The present invention provides a CdSe / Cd with high polarization degree and high luminous efficiency. x Zn 1-x The preparation method of S quantum rods is to continuously grow CdS outside the CdSe core by controlling the addition order of different reactants. x Zn 1-x The S alloy shell structure effectively passivates the core surface while reducing surface defects caused by shell lattice mutations, thereby improving its luminous efficiency. The entire preparation process of the quantum rod is carried out in a three-necked flask filled with inert gas (nitrogen or argon) and stirred with a magnetic stirrer. The steps are as follows:
[0028] (1) preparing a CdO precursor solution under an inert gas environment and heating it to a reaction temperature of 350±20° C., then sequentially injecting tri-n-octylphosphine and a CdSe precursor solution to obtain a first mixed solution;
[0029] In this step, the CdO precursor solution is a mixed solution formed by heating and dissolving CdO, octadecylphosphonic acid, hexylphosphonic acid, and tri-n-octylphosphine oxide, and the mass ratio of CdO, octadecylphosphonic acid, hexylphosphonic acid, and tri-n-octylphosphine oxide is 1:10-18:3-5:130-190;
[0030] In this step, the mass of tri-n-octylphosphine injected alone is 0.3 to 0.5 times the mass of the CdO precursor solution;
[0031] In this step, the CdSe precursor solution is a mixed solution formed by heating and dissolving CdSe seeds, sulfur powder, and tri-n-octylphosphine, and the mass ratio of CdSe seeds, sulfur powder, and tri-n-octylphosphine is 1:2-3.5:100-160;
[0032] In this step, the amount of CdSe precursor solution added is 0.3 to 0.5 times the mass of the CdO precursor solution;
[0033] (2) slowly adding a Zn precursor solution to the first mixed solution of step (1) at a dropping rate of 6 to 12 mL / h to obtain a second mixed solution;
[0034] In this step, the Zn precursor solution is a mixed solution formed by heating and dissolving zinc acetate, octadecene, and oleic acid, and the mass ratio of zinc acetate, octadecene, and oleic acid is 1:3-5:3.5-6.
[0035] In this step, the amount of Zn precursor solution added is 0.9 to 1.3 times the mass of the CdO precursor solution;
[0036] (3) Octadecene was first injected into the second mixed solution of step (2) to dilute it, and the reaction temperature was cooled to 300±20°C, and then the mixed solution of octadecene and S precursor solution was slowly added dropwise at a dropping rate of 4-8 mL / h, and the reaction temperature was 300±20°C. After the addition was completed, the reaction was terminated to obtain CdSe / Cd x Zn 1-x S quantum rod, where 0<x<1;
[0037] In this step, the total amount of octadecene is 0.5 to 0.8 times the mass of the Zn precursor solution added in step (2), and 2 / 3 of the octadecene is added for dilution, and the remaining 1 / 3 of the octadecene is mixed with the S precursor solution;
[0038] In this step, the S precursor solution is a mixed solution formed by heating and dissolving sulfur powder and tri-n-octylphosphine, and the mass ratio of sulfur powder to tri-n-octylphosphine is 1:10-15;
[0039] In this step, the amount of S precursor solution added is 0.1 to 0.15 times the mass of the Zn precursor solution added in step (2);
[0040] (4) After the reaction is completed, cool to room temperature and purify the obtained CdSe / Cd x Zn 1-x S quantum rod;
[0041] In this step, the anti-solvent method is used to purify the quantum rods. The specific method is: first use n-hexane to dilute the CdSe / Cd x Zn 1-x S quantum rod solution, then add ethanol to form a suspension, and then centrifuge to settle the suspension, collect the precipitate, and the precipitate is CdSe / Cd x Zn 1-x S quantum rods, the precipitate was dissolved in n-hexane and stored.
[0042] In the above preparation process, the present invention first injects the CdSe precursor solution into the Cd precursor solution, and then slowly adds the Zn precursor solution. At this time, the Cd and Zn elements in the Cd precursor solution and the Zn precursor solution begin to combine with the S element in the CdSe precursor solution to form CdSe precursor solution. x Zn 1-x The S shell gradually wraps around the CdSe core; in addition, since the Zn precursor will slowly agglomerate when mixed with the TOPO solution, after injecting a certain amount of Zn precursor, it is necessary to add octadecene to dilute the TOPO to prevent the Zn precursor from agglomerating, and then continue to add the S precursor solution to maintain the further epitaxial growth of the shell, thus achieving uninterrupted epitaxial growth of CdSe. x Zn 1-x S shell.
[0043] CdSe / Cd prepared by the above method x Zn 1-x S quantum rod, including CdSe core and Cd coated outside the CdSe core x Zn 1-x S shell, and CdSe / Cd x Zn 1-x The photoluminescence quantum yield of the S quantum rod reaches more than 90%, and the polarization degree reaches more than 0.75.
[0044] In addition, it should be noted that the CdSe seeds required for configuring the CdSe precursor solution in the above step (1) can be purchased from the market or synthesized by oneself. The CdSe seeds used in the present invention are synthesized by oneself, and the synthesis method is specifically as follows: tri-n-octylphosphine oxide, octadecylphosphonic acid, and CdO are mixed in a mass ratio of 40 to 60:3 to 6:1, and heated in an inert gas environment until dissolved; then tri-n-octylphosphine is added, and the amount of tri-n-octylphosphine added is 20 to 30 times the mass of CdO, and the temperature is continued to rise to 370±20°C; then Se precursor solution is injected, and the amount of Se precursor solution added is 3 to 6 times the mass of CdO, and the mass ratio of Se to tri-n-octylphosphine in the Se precursor solution is 1:6 to 9; react for 1 to 3 minutes, then cool to room temperature, purify using an anti-solvent method, and evaporate the solvent to obtain CdSe seeds.
[0045] Example 1
[0046] This embodiment prepares a CdSe / Cd x Zn 1-x S quantum rod, the specific process is as follows:
[0047] (1) Add 0.019 g of cadmium oxide, 0.265 g of octadecylphosphonic acid, 0.08 g of hexylphosphonic acid, and 3 g of tri-n-octylphosphine oxide to a three-necked flask filled with nitrogen, heat and dissolve to prepare a CdO precursor solution, then heat to a reaction temperature of 350° C., then first inject 1.8 mL of tri-n-octylphosphine, and then inject 1.369 g of CdSe precursor solution, the CdSe precursor solution being a mixed solution formed by heating and dissolving CdSe seeds, sulfur powder, and tri-n-octylphosphine in a mass ratio of 1:2.9:133 to obtain a first mixed solution;
[0048] (2) Next, 4 mL of a Zn precursor solution was slowly added dropwise to the first mixed solution of step (1) at a rate of 9 mL / h, wherein the Zn precursor solution was a mixed solution prepared by heating and dissolving zinc acetate, octadecene, and oleic acid in a mass ratio of 1:4.3:4.9 to obtain a second mixed solution;
[0049] (3) 2 mL of octadecene was first injected into the second mixed solution of step (2) for dilution, and then a mixed solution of 1 mL of octadecene and 0.5 mL of S precursor solution was added dropwise at a rate of 6 mL / h. The S precursor solution was a mixed solution formed by heating and dissolving sulfur powder and tri-n-octylphosphine in a mass ratio of 1:13. After the addition was completed, the reaction was stopped to obtain a mixture containing CdSe / Cd x Zn 1-x Mixed solution of S quantum rods;
[0050] (4) After the reaction is completed, the temperature is cooled to room temperature, and the obtained CdSe / Cd is purified by anti-solvent method. x Zn 1-x S quantum rods, namely, the CdSe / Cd obtained in step (3) is diluted with n-hexane. x Zn 1-x S quantum rod solution, then add ethanol to form a suspension, and then centrifuge to settle the suspension, collect the precipitate, and the precipitate is CdSe / Cd x Zn 1-x S quantum rods, the precipitate was dissolved in n-hexane and stored.
[0051] Example 2
[0052] This embodiment prepares a CdSe / Cd x Zn 1-x S quantum rod, the specific process is as follows:
[0053] (1) Add 0.02 g of cadmium oxide, 0.2 g of octadecylphosphonic acid, 0.065 g of hexylphosphonic acid, and 2.8 g of tri-n-octylphosphine oxide to a three-necked flask filled with nitrogen, heat and dissolve to prepare a CdO precursor solution, then heat to a reaction temperature of 340° C., then first inject 1.2 mL of tri-n-octylphosphine, and then inject 1.03 g of CdSe precursor solution, and the CdSe precursor solution is a mixed solution formed by heating and dissolving CdSe seeds, sulfur powder, and tri-n-octylphosphine in a mass ratio of 1:2:100 to obtain a first mixed solution;
[0054] (2) Next, 3.3 mL of a Zn precursor solution was slowly added dropwise to the first mixed solution of step (1) at a rate of 6 mL / h, wherein the Zn precursor solution was a mixed solution formed by heating and dissolving zinc acetate, octadecene, and oleic acid in a mass ratio of 1:3.5:4 to obtain a second mixed solution;
[0055] (3) Immediately after that, 1.5 mL of octadecene was injected into the second mixed solution of the above step (2) for dilution, and then a mixed solution of 0.75 mL of octadecene and 0.35 mL of S precursor solution was added dropwise at a rate of 5 mL / h. The S precursor solution was a mixed solution formed by heating and dissolving sulfur powder and tri-n-octylphosphine in a mass ratio of 1:10. After the addition was completed, the reaction was stopped to obtain a mixture containing CdSe / Cd x Zn 1-x Mixed solution of S quantum rods;
[0056] (4) After the reaction is completed, the temperature is cooled to room temperature, and the obtained CdSe / Cd is purified by anti-solvent method. x Zn 1-xS quantum rods, namely, the CdSe / Cd obtained in step (3) is diluted with n-hexane. x Zn 1-x S quantum rod solution, then add ethanol to form a suspension, and then centrifuge to settle the suspension, collect the precipitate, and the precipitate is CdSe / Cd x Zn 1-x S quantum rods, the precipitate was dissolved in n-hexane and stored.
[0057] Example 3
[0058] This embodiment prepares a CdSe / Cd x Zn 1-x S quantum rod, the specific process is as follows:
[0059] (1) Add 0.02 g of cadmium oxide, 0.35 g of octadecylphosphonic acid, 0.10 g of hexylphosphonic acid, and 3.6 g of tri-n-octylphosphine oxide to a three-necked flask filled with nitrogen, heat and dissolve to prepare a CdO precursor solution, then heat to a reaction temperature of 370° C., then first inject 2.4 mL of tri-n-octylphosphine, and then inject 1.53 g of CdSe precursor solution, wherein the CdSe precursor solution is formed by heating and dissolving CdSe seeds, sulfur powder, and tri-n-octylphosphine in a mass ratio of 1:3:150 to obtain a first mixed solution;
[0060] (2) Next, 5.4 mL of a Zn precursor solution was slowly added dropwise to the first mixed solution of step (1) at a rate of 12 mL / h, wherein the Zn precursor solution was a mixed solution prepared by heating and dissolving zinc acetate, octadecene, and oleic acid in a mass ratio of 1:5:6 to obtain a second mixed solution;
[0061] (3) Immediately after that, 3.3 mL of octadecene was injected into the second mixed solution of the above step (2) for dilution, and then a mixed solution of 1.7 mL of octadecene and 0.79 mL of S precursor solution was added dropwise at a rate of 8 mL / h. The S precursor solution was a mixed solution formed by heating and dissolving sulfur powder and tri-n-octylphosphine in a mass ratio of 1:15. After the addition was completed, the reaction was stopped to obtain a mixture containing CdSe / Cd x Zn 1-x Mixed solution of S quantum rods;
[0062] (4) After the reaction is completed, the temperature is cooled to room temperature, and the obtained CdSe / Cd is purified by anti-solvent method. x Zn 1-x S quantum rods, namely, the CdSe / Cd obtained in step (3) is diluted with n-hexane. x Zn 1-xS quantum rod solution, then add ethanol to form a suspension, and then centrifuge to settle the suspension, collect the precipitate, and the precipitate is CdSe / Cd x Zn 1-x S quantum rods, the precipitate was dissolved in n-hexane and stored.
[0063] Comparative Example 1
[0064] This comparative example prepares CdSe / CdS quantum rods, and the preparation process is as follows:
[0065] 0.019 g of cadmium oxide, 0.265 g of octadecylphosphonic acid, 0.08 g of hexylphosphonic acid, and 3 g of tri-n-octylphosphine oxide were added to a three-necked flask filled with nitrogen and heated to dissolve to prepare a CdO precursor solution. The temperature was then raised to a reaction temperature of 350°C. 1.8 mL of tri-n-octylphosphine was then injected first, followed by a CdSe precursor solution formed by heating and dissolving 10 mg of CdSe seeds, 29 mg of sulfur powder, and 1.6 mL of tri-n-octylphosphine. The reaction was allowed to proceed for 10 minutes. After the reaction was completed, the temperature was lowered to room temperature, and the resulting CdSe / CdS quantum rods were purified using an antisolvent method.
[0066] The CdSe / CdS quantum rod prepared in this comparative example includes a CdSe core and a CdS shell layer covering the outside of the CdSe core.
[0067] Comparative Example 2
[0068] This comparative example prepares CdSe / CdS / ZnS quantum rods, and the preparation process is as follows:
[0069] (1) Add 0.019 g of cadmium oxide, 0.265 g of octadecylphosphonic acid, 0.08 g of hexylphosphonic acid, and 3 g of tri-n-octylphosphine oxide to a three-necked flask filled with nitrogen, heat and dissolve to prepare a CdO precursor solution, then heat to a reaction temperature of 350°C, and then inject 1.8 mL of tri-n-octylphosphine first, and then inject a CdSe precursor solution formed by heating and dissolving 10 mg of CdSe seeds, 29 mg of sulfur powder, and 1.6 mL of tri-n-octylphosphine, and react for 5 minutes to obtain CdSe / CdS quantum rods; after the reaction is completed, cool to room temperature, and purify the CdSe / CdS quantum rods by an anti-solvent method;
[0070] (2) 100 mg of CdSe / CdS quantum rods were mixed with 5 mL of octadecene, heated to 300 ° C, and a mixed solution of 4 mL of Zn precursor solution (zinc acetate, octadecene, and oleic acid were prepared in a mass ratio of 1:4.3:4.9 and heated to dissolve) and 0.5 mL of S precursor solution (sulfur powder and tri-n-octylphosphine were prepared in a mass ratio of 1:13 and heated to dissolve) was added dropwise at a rate of 2 mL / h. After the addition was completed, the reaction was stopped to obtain a mixed solution containing CdSe / CdS / ZnS quantum rods;
[0071] (3) After the reaction is completed, the temperature is lowered to room temperature, and the obtained CdSe / CdS / ZnS quantum rods are purified by an anti-solvent method and stored in n-hexane.
[0072] The CdSe seeds used in the preparation process of the above Examples 1-3 and Comparative Examples 1 and 2 were self-synthesized. The specific synthesis process was as follows: 3 g of tri-n-octylphosphine oxide, 0.28 g of octadecylphosphonic acid, and 0.06 g of CdO were mixed and heated in an inert gas environment until dissolved; then 1.8 mL of tri-n-octylphosphine was added and the temperature was continued to rise to 370°C; then a Se precursor solution was injected, and the Se precursor solution was mixed with 0.029 g of Se and 0.22 g of tri-n-octylphosphine; the reaction was allowed to proceed for 1 minute, and then the mixture was cooled to room temperature, purified using an anti-solvent method, and the solvent was evaporated to obtain CdSe seeds.
[0073] Reference Figure 1 , the CdSe / Cd prepared in Examples 1-3 above x Zn 1-x The structure of the S quantum rod includes a CdSe core and a Cd x Zn 1-x S shell structure. To verify the prepared CdSe / Cd x Zn 1-x S quantum rods have Figure 1 The structure shown in FIG1 was also observed by HAADF-STEM microscopy. x Zn 1-x The S quantum rods were detected and the obtained HAADF-STEM micrographs were as follows: Figure 2 As shown. Figure 2 The distribution of the elements in the quantum rod shows that Se and some Cd elements are concentrated in the center of the quantum rod to form a CdSe core; S, Zn and some Cd elements are doped and distributed outside the quantum rod core to form a Cd x Zn 1-x In addition, the CdSe / Cd prepared in Example 1 was also examined using atomic resolution transmission electron microscopy. x Zn 1-xThe atomic resolution TEM images obtained by S quantum rod detection are shown in the following figure. Figure 3 As shown. Figure 3 It can be seen that the lattice of the quantum rod shell is clear and regular, without obvious defects and distortions, indicating that the Zn element and the Cd element are fused together to form the Cd x Zn 1-x S alloy shell structure.
[0074] The quantum rods prepared in Example 1 and Comparative Examples 1 and 2 were tested for photoluminescence quantum yield (PLQY) and polarization. Ten samples were prepared for each of these tests. The samples used for PLQY testing were 20 mg / mL quantum rod-n-hexane solutions, tested using an Ocean Optics integrating sphere system. The samples used for luminescence polarization testing were 5% wt quantum rod-polymer dispersion films (wherein the polymer was poly(butyl methacrylate)-co-(isobutylmethacrylate) in methylbenzene). The films were stretched twice their length in a single direction to align the orientation of the quantum rods. The results for photoluminescence quantum yield and polarization are shown in Tables 1 and 2, respectively.
[0075] Table 1 Photoluminescence quantum yield test results of Example 1 and Comparative Examples 1 and 2
[0076]
[0077] Table 2 Polarization degree test results of Example 1 and Comparative Examples 1 and 2
[0078]
[0079] The test results of Table 1 and Table 2 are analyzed: the CdSe / Cd prepared in Example 1 of the present invention x Zn 1-x The photoluminescence quantum yield (PLQY) and luminescence polarization of CdSe / CdS quantum rods are significantly higher than those of CdSe / CdS quantum rods and CdSe / CdS / ZnS quantum rods. x Zn 1-x The photoluminescence quantum yield (PLQY) of the S quantum rod can reach more than 90%, and the luminescence polarization degree can reach more than 0.75.
[0080] In addition, Example 1 of the present invention also tests the CdSe / Cd x Zn 1-x The absorption and emission spectra of S quantum rods are tested, such as Figure 4 As shown. Figure 4 It can be seen that: CdSe / Cdx Zn 1-x The emission wavelength of the S quantum rod is around 600nm, and it can emit red light, which can make silicon-based solar cells produce a better response; and this quantum rod material has the characteristics of wide spectrum absorption, which can absorb most of the sunlight spectrum energy, which is conducive to obtaining higher energy conversion efficiency.
[0081] It should be noted that the parts not described in the present invention can be implemented by adopting or drawing on existing technologies.
[0082] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the scope of protection of the present invention.
Claims
1. A high polarization degree and high luminous efficiency CdSe / Cd x Zn 1-x The method for preparing S quantum rods is characterized in that: Including steps: (1) preparing a CdO precursor solution under an inert gas environment and heating it to a reaction temperature of 350±20° C., then sequentially injecting tri-n-octylphosphine and a CdSe precursor solution to obtain a first mixed solution; (2) slowly adding a Zn precursor solution to the first mixed solution of step (1) to obtain a second mixed solution; (3) Octadecene was first injected into the second mixed solution of step (2) to dilute it, and the reaction temperature was cooled to 300±20°C, and then the mixed solution of octadecene and S precursor solution was slowly added dropwise. After the addition was completed, the reaction was stopped to obtain CdSe / Cd x Zn 1-x S quantum rod, where 0<x<1; (4) After the reaction is completed, cool to room temperature and purify the obtained CdSe / Cd x Zn 1-x S quantum rod.
2. A CdSe / Cd with high polarization degree and high luminous efficiency according to claim 1 x Zn 1-x The method for preparing S quantum rods is characterized in that: In the step (1), the CdO precursor solution is a mixed solution formed by heating and dissolving CdO, octadecylphosphonic acid, hexylphosphonic acid, and tri-n-octylphosphine oxide, and the mass ratio of CdO, octadecylphosphonic acid, hexylphosphonic acid, and tri-n-octylphosphine oxide is 1:10-18:3-5:130-190.
3. A CdSe / Cd with high polarization degree and high luminous efficiency according to claim 1 x Zn 1-x The method for preparing S quantum rods is characterized in that: The mass of tri-n-octylphosphine injected separately in step (1) is 0.3 to 0.5 times the mass of the CdO precursor solution.
4. The high polarization degree and high luminous efficiency CdSe / Cd according to claim 1 x Zn 1-x The method for preparing S quantum rods is characterized in that: In the step (1), the CdSe precursor solution is a mixed solution formed by heating and dissolving CdSe seeds, sulfur powder, and tri-n-octylphosphine, the mass ratio of CdSe seeds, sulfur powder, and tri-n-octylphosphine is 1:2-3.5:100-160, and the amount of CdSe precursor solution added is 0.3-0.5 times the mass of the CdO precursor solution.
5. The high polarization degree and high luminous efficiency CdSe / Cd according to claim 1 x Zn 1-x The method for preparing S quantum rods is characterized in that: In the step (2), the Zn precursor solution is a mixed solution formed by heating and dissolving zinc acetate, octadecene, and oleic acid, the mass ratio of zinc acetate, octadecene, and oleic acid is 1:3-5:3.5-6, and the amount of the Zn precursor solution added is 0.9-1.3 times the mass of the CdO precursor solution.
6. The high polarization degree and high luminous efficiency CdSe / Cd according to claim 1 x Zn 1-x The method for preparing S quantum rods is characterized in that: The total amount of octadecene in step (3) is 0.5 to 0.8 times the mass of the Zn precursor solution added in step (2), and 2 / 3 of the octadecene is added for dilution for the first time, and the remaining 1 / 3 of the octadecene is mixed with the S precursor solution.
7. The high polarization degree and high luminous efficiency CdSe / Cd according to claim 1 x Zn 1-x The method for preparing S quantum rods is characterized in that: The S precursor solution in step (3) is a mixed solution formed by heating and dissolving sulfur powder and tri-n-octylphosphine, the mass ratio of sulfur powder to tri-n-octylphosphine is 1:10-15, and the amount of the S precursor solution added is 0.1-0.15 times the mass of the Zn precursor solution added in step (2).
8. The CdSe / Cd with high polarization degree and high luminous efficiency according to claim 1 x Zn 1-x The method for preparing S quantum rods is characterized in that: In the step (2), the dropwise addition rate of the Zn precursor solution is 6 to 12 mL / h, and the dropwise addition rate of the mixed solution of octadecene and the S precursor solution is 4 to 8 mL / h.
9. A high polarization degree and high luminous efficiency CdSe / Cd x Zn 1-x The S quantum rod is prepared by the method according to any one of claims 1 to 8, characterized in that: It includes a CdSe core and a Cd x Zn 1-x S shell.
10. The CdSe / Cd with high polarization degree and high luminous efficiency according to claim 9 x Zn 1-x S quantum rod, characterized in that The CdSe / Cd x Zn 1-x The photoluminescence quantum yield of the S quantum rod reaches more than 90%, and the polarization degree reaches more than 0.75.
